2022
DOI: 10.1002/adom.202102783
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon‐Induced Disorder Engineering for Robust Optical Sensors

Abstract: Optical metasurfaces address a plethora of applications in planar optics, as they enable precise control of the phase, amplitude, and polarization of light at nanoscale interaction lengths. However, their implementation requires surface nanostructuring, based on complex design and fabrication methods. In addition, exploiting narrow spectral features, e.g., for sensing, is accompanied by high demands in terms of precise post‐process alignments of probing light—impractical for compact optical systems. Here, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…However, despite the low Q -factors of the SR-SPPs ranging from Q = 33 to Q = 83 for t m = 20 nm and t m = 40 nm, respectively, the presented approach enables us to obtain very sharp resonances. The sharpness arises due to the delocalized nature of the system response under coherent illumination on large areas (in the range of several tens of mm 2 ) . The results presented in this work thus represent a first step toward the facile utilization of SR-SPPs in planar optical sensing devices with extraordinary performance in detecting surface binding events in the future.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, despite the low Q -factors of the SR-SPPs ranging from Q = 33 to Q = 83 for t m = 20 nm and t m = 40 nm, respectively, the presented approach enables us to obtain very sharp resonances. The sharpness arises due to the delocalized nature of the system response under coherent illumination on large areas (in the range of several tens of mm 2 ) . The results presented in this work thus represent a first step toward the facile utilization of SR-SPPs in planar optical sensing devices with extraordinary performance in detecting surface binding events in the future.…”
Section: Discussionmentioning
confidence: 79%
“…2 Recently, it has been shown that a disorder-engineered metasurface consisting of silver nanoparticles (AgNPs) in close proximity to a thin silver film can enable high optical sensing performance. 17 Due to the selective scattering mediated by the metasurface, the SPP modes propagating on the silver film create a sharp resonance in the reflection signal, which is highly sensitive to the refractive index of the analyte. The width of this resonance is around 2 orders of magnitude narrower compared to the initial SPP resonance without the metasurface and is largely governed by the divergence of the laser used for fabrication and probing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14,15 ] Metasurfaces built from thin subwavelength structures have drawn attention as an advanced tool to control the properties of light. [ 16–18 ]…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Metasurfaces built from thin subwavelength structures have drawn attention as an advanced tool to control the properties of light. [16][17][18] In symmetric waveguide gratings, large sensitivity is reported for odd modes providing a node of minimized interaction with the center grating. [19] The highest sensitivity in waveguide gratings, however, is reported for dielectric bound state in the continuum (BICs) showing zero diffraction to the radiation continuum.…”
mentioning
confidence: 99%